Embryonic ionizing radiation exposure results in expression alterations of genes associated with cardiovascular and neurological development, function, and disease and modified cardiovascular function in zebrafish - Freeman, Jennifer L.; Weber, Gregory J.; Peterson, Samuel M.; Nie, Linda H. (Frontiers in Genetics, 2014)
The relationship between ionizing radiation (IR) and carcinogenesis is long established, but recently the association between IR and other diseases is starting to be recognized. Currently, there is limited information on the genetic mechanisms governing the role of IR in non-cancer related adverse health effects and in regards to an early developmental exposure. In this study, zebrafish embryos were exposed to a range of IR doses (0, 1, 2, 5, 10 Gy) at 26 hours post fertilization (hpf). No significant increase in mortality or hatching rate was observed, but a significant decrease in total larval length, head length, and eye diameter was observed in the 10 Gy dose. Transcriptomic analysis was conducted at 120 hpf to compare gene expression profiles between the control and highest IR dose at which no significant differences were observed in morphological measurements (5 Gy). 253 genes with well-established function or orthology to human genes were significantly altered. Gene ontology and molecular network analysis revealed enrichment of genes associated with cardiovascular and neurological development, function, and disease. Expression of a subset of genetic targets with an emphasis on those associated with the cardiovascular system was assessed using qPCR to confirm altered expression at 5 Gy and then to investigate alterations at lower doses (1 and 2 Gy). Strong correlation between microarray and qPCR expression values was observed, but zebrafish exposed to 1 or 2 Gy resulted in a significant expression alteration in only one of these genes (LIN7B). Moreover, heart rate was analyzed through 120 hpf following IR dosing at 26 hpf. A significant decrease in heart rate was observed at 10 Gy, while a significant increase in heart rate was observed at 1, 2, and 5 Gy. Overall these findings indicate IR exposure at doses below those that induce gross morphological changes alters heart rate and expression of genes associated with cardiovascular and neurological functions.